Formation mechanism of Al-Zn-Mg-Cu alloy fabricated by laser-arc hybrid additive manufacturing: Microstructure evaluation and mechanical properties - Liu, Dehua; Wu, Dongjiang; Wang, Ruzheng; Shi, Jingan; Niu, Fangyong; Ma, Guangyi (Additive manufacturing, 2022)
A novel additive manufacturing followed by a hybrid process involving pulsed laser and tungsten inert gas (TIG) arc was proposed to balance the element vaporization, microstructure uniformity, and mechanical properties of the Al-Zn-Mg-Cu alloy. The amount of vaporized Zn in the laser-arc hybrid additive manufacturing (LAHAM) reduced by merely 2.5%, whereas the Zn vaporization loss of the WAAM specimens reached up to 8.3%. Compared with the grain sizes of specimen obtained via WAAM, those obtained via LAHAM decreased by approximately two times. The < 100 > texture in the LAHAM specimen was decreased significantly, due to the appearance of equiaxed grains and grain refinement. Furthermore, in contrast to WAAM specimen, the eutectics contained Al, Zn, Mg and Cu were evenly distributed in the LAHAM specimen, resulting in uniform element distribution. Nano-precipitates were dispersedly distributed within the grains in the LAHAM specimen, whereas they merely appeared around the grain boundaries in the WAAM specimen. Owing to microstructure changes, LAHAM improved the ultimate tensile strength and yield strength by up to 11.4% and 29.9%, as compared with WAAM. The substantial improvement in yield strength was primarily attributed to precipitation strengthening, instead of grain boundary strengthening or solid solution strengthening. [Display omitted]